Tahapan-tahapan Laju Perkembangan Gerak dan Motorik pada Anak Usia Dini - Ahadin Ahadin (Universitas Syiah Kuala, 2021)
The development of motor movement is a change in motor behavior that occurs due to the process of maturity and the environment. Maturity is a change that occurs in the body over a period of time. What affects children's motor development are family, playmates, and the environment. Families, especially parents, are usually the ones who have the most influence on children's lives. Most of the children who want their parents to be happy with themselves and their efforts, Playmates, can influence the child to move stronger, and more freely. The environment in which children live in motor development, fine motor skills or gross motor skills is very direct and strong, especially if children are given formal education. We can interpret motor skills as a capacity possessed by individuals to be able to develop the ability of the abilities possessed by these individuals in an effort to be able to enhance or accelerate the mastery or proficiency of a skill. Children who have good motor skills, it will be easier to master motor skills, so that motor skills obtained through a process associated with the training process, or improvement can be through experience if changes in motor behavior are obtained through the learning process, then mastery of a child's physical motor movements will be permanent.